2011
DOI: 10.1111/j.1399-5618.2011.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Does stage of illness impact treatment response in bipolar disorder? Empirical treatment data and their implication for the staging model and early intervention

Abstract: Those individuals at the earliest stages of illness consistently had a more favourable response to treatment. This is consistent with the staging model and underscores the need to support a policy of early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
2
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 49 publications
4
139
2
14
Order By: Relevance
“…Similarly, a clinical trial of cognitive behavioral therapy showed that only patients who had fewer than 12 episodes of illness improved [10]. Moreover, a study showed that response rates for olanzapine in acute mood episodes or during the maintenance phase were significantly higher among individuals with less than five previous episodes [11]. In addition, a study with thirty-five treatment-resistant patients with bipolar disorder reported that response to lamotrigine monotherapy was associated with fewer hospitalizations [12].…”
Section: Treatment Refractorinessmentioning
confidence: 99%
“…Similarly, a clinical trial of cognitive behavioral therapy showed that only patients who had fewer than 12 episodes of illness improved [10]. Moreover, a study showed that response rates for olanzapine in acute mood episodes or during the maintenance phase were significantly higher among individuals with less than five previous episodes [11]. In addition, a study with thirty-five treatment-resistant patients with bipolar disorder reported that response to lamotrigine monotherapy was associated with fewer hospitalizations [12].…”
Section: Treatment Refractorinessmentioning
confidence: 99%
“…Os efeitos progressivos no sistema nervoso central (SNC), assim como interações entre centro e periferia, são o enfoque escolhido pelo professor Berk, na Austrália, com destaque para "neuroproteção" e "neuroprogressão" 2,17 . Isso se alinha a dados recentes que sugerem que alguma versão de estadiamento clínico possa ser útil para prescrição individual de tratamento [18][19][20] .…”
Section: Introductionunclassified
“…7 There is substantial evidence that the number of previous affective episodes is a risk factor for episode recurrence, chronicity, and suicide; thus, appropriate early treatment would likely decrease the risk of these negative outcomes. 6 Most evidence-based BD guidelines do not address treatment specifically in the context of the early stages.…”
Section: Psychopharmacologicalmentioning
confidence: 99%
“…Because issues of recovery can significantly affect disability, quality of life, and outcome, early intervention for first-episode individuals with BD is clearly an important objective. 6 An assessment of quality of life after recovery from a first manic episode indicated that quality of life is related to length of illness and severity of depressive symptoms at both baseline and 6 months, as well as to the number of depressive episodes (Table 3), 40 indicating a need for aggressive treatment of depressive symptoms in this population.…”
Section: First Episode Of Mania (Stage Ii)mentioning
confidence: 99%
See 1 more Smart Citation